Life cycle assessment of soybeans production and processing system into soy oil using solvent extraction process. (1st January 2013) - Jekayinfa, S.O.; Olaniran, J.A.; Sasanya, B.F.
Agricultural operations have been indicated to be some of the major emitters of greenhouse gases (GHG), particularly methane (CH4 ) and nitrous oxide (N2 O) around the globe, and it is important to determine the quantity emitted and how they can be reduced. The environmental impacts associated with field production and industrial processing of soybean into crude vegetable oil in Nigeria was therefore studied using the life cycle impacts assessment tool. The emission from the various inputs into the system was aggregated into a large inventory table. The functional unit was defined as one kilogram of soybean. The environmental impact categories used in this study are global warming, acidification, eutrophication and ozone layer depletion. Of these four environmental impacts, global warming has the highest impact score of 4.7516E-01 kg CO2 equivalent, followed by eutrophication (1.6414E-04 kg NO3 equivalent). Ozone layer depletion has the lowest environmental impact score of –2.8207E-07 kg R11 equivalent. The high impact score of global warming is due to the high emission of CO2 gas from fossil fuel and biomass combustion during field operations and processing of soybeans.